A dimensão estratégica da política externa dos Estados Unidos no Caribe (1898-1904) - Farias, Flávio José de Moura (2008)
After the 1898 Spanish-American War, the United States established naval bases in Cuba and Porto Rico, and started to build an interoceanic canal in Panama. The purpose of this research is, therefore, to analyze how the United States obtained these bases, their importance to the defense of the Panama Canal and how they connected with the American foreign policy for the Caribbean set up by presidents William McKinley and Theodore Roosevelt